The Svensson versus McCallum and Nelson Controversy Revisited in the BMW Framework - Peter Bofinger; Eric Mayer (University of Würzburg, Department of Economics, 2006)
This note shows that the Svensson versus McCallum and Nelson controversy battled in the Federal Reserve Bank of St. Louis Review (September/ October 2005) can be mapped into a static version of a New Keynesian macro model that consists of an IS-equation, a Phillips curve and an inflation targeting central bank (e.g., Bofinger, Mayer, Wollmershäuser, (2006); Walsh (2002)). As a contribution to literature we supplement the controversy by a forceful graphical analysis. The general debate centers on the question by which notion monetary policy should be implemented. The two sides have fundametaly opposite views on this issue. Svensson argues for targeting rules as a notion of optimal monetary policy, whereas McCallum and Nelson promote simple instrument rules. In this note we systematically analyze these two categories of monetary policy rules. In particular we show that the rule discussed by McCallum and Nelson (2005) imposes different degrees of variability on the economy compared to a targeting rule when monetary policy falls prey to measurement error. To our opinion the rule developed by McCallum and Nelson contradicts the original idea of simple rules as a heuristic for monetary policy making and should be rebutted for practical reasons .
Keywords: E30; E58; E52; 330; inflation targeting; monetary policy rules; New Keynesian macroeconomics; central bank strategies